Analisis Pengaruh Sistem Informasi Akuntansi Berbasis E-commerce terhadap Kinerja Bisnis UMKM - Eda Vasha; Rustam Hanafi (LPPM UBSI Kampus Kota Tegal, 2026)
Digital transformation has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt e-commerc based Accounting Information Systems (AIS) in order to improve operational efficiency and business competitiveness. This study aims to examine the effects of perceived ease of use, perceived usefulness, trust, and perceived risk on MSME business performance. A quantitative approach was employed using a survey method involving 100 MSME owners who have utilized e-commerce based AIS for at least one year. Data were collected through Likert-scale questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that perceived ease of use, perceived usefulness, and trust have a positive and significant effect on MSME business performance. In contrast, perceived risk has a significant negative effect. These findings highlight the importance of ease of use, perceived benefits, and trust in the implementation of e-commerce based AIS, as well as the need for effective risk management to optimize MSME business performance.